The relationship between gonadotropin releasing hormone and ovulation inducing factor/nerve growth factor receptors in the hypothalamus of the llama - Rodrigo A. Carrasco; Jaswant Singh; Gregg P. Adams (BMC, 2018)
Abstract Background A molecule identical to nerve growth factor, with ovulation-inducing properties has been discovered in the seminal plasma of South American camelids (ovulation-inducing factor/nerve growth factor; OIF/NGF). We hypothesize that the ovulatory effect of OIF/NGF is initiated at the level of the hypothalamus, presumably by GnRH neurons. The objective of the present study was to determine the structural relationship between GnRH neurons and neurons expressing high- and low-affinity receptors for NGF (i.e., TrkA and p75, respectively) in the hypothalamus. Methods Mature llamas (n = 4) were euthanized and their hypothalamic tissue was fixed, sectioned, and processed for immunohistochemistry on free-floating sections. Ten equidistant sections per brain were double stained for immunofluorescence detection of TrkA and GnRH, or p75 and GnRH. Results Cells immunoreactive to TrkA were detected in most hypothalamic areas, but the majority of cells were detected in the diagonal band of Broca (part of the ventral forebrain) and the supraoptic nuclei and periventricular area. The number of cells immunoreactive to p75 was highest in the diagonal band of Broca and lateral preoptic areas and least in more caudal areas of the hypothalamus (p < 0.05) in a pattern similar to that of TrkA. A low proportion of GnRH neurons were immunoreactive to TrkA (2.5% of total GnRH cells), and no co-localization between GnRH and p75 was detected. GnRH neuron fibers were detected only occasionally in proximity to TrkA immunopositive neurons. Conclusions Results do not support the hypothesis that the effect of OIF/NGF is driven by a direct interaction with GnRH neurons, but rather provide rationale for the hypothesis that interneurons exist in the hypothalamus that mediate OIF/NGF-induced ovulation.